Fundamental And Macroeconomic Influence On Jakarta Islamic Index (Jii) Stock Prices For The 2020-2022 Period - Margaretna, Lisa; Ul Husaen, Fuad Dhiya (IQTISHADUNA, 2024)
The Covid-19 pandemic that has hit the world, including Indonesia, has had a major impact on the economy. The impact that occurs in various sectors, one of which is the capital market sector. The capital market experiences ups and downs in stock prices which are important aspects of the capital market. Stock price movements can certainly be triggered by internal factors and external factors. This study aims to determine the fundamental and macroeconomic influences on the share prices of companies listed on the Jakarta Islamic index (JII) for 2020-2022. This research is a quantitative research using secondary data collection methods. This study also used a sampling method, namely Purpose Sampling. Then the data obtained is processed using the SPSS tool version 23. The analysis technique used is multiple linear regression. The results of this study show that Debt To Equity Ratio (DER), Exchange Rate and GDP have no effect on stock prices. While Earnings per Share (EPS), Price to Book Value (PBV) has a positive effect on stock prices.